Distribuição do ictioplâncton em diferentes micro-habitats do médio Rio Uruguai, Brasil - Martine, Gabriela (2019)
Research related to ichthyoplankton provides relevant information about its initial development, but for the Uruguay River basin, little is known about which environments are preferred by fish larvae during the early stages of their life cycle. From this, the objective of this work was to evaluate five microhabitats in three sample stations in the middle Uruguay River, located in the municipalities of Porto Mauá, Porto Vera Cruz and São Nicolau, RS, respectively. Monthly collections were carried out at night, from November 2017 to January 2018, totaling 180 samplings. The spatial distribution of the sampling stations lies in a stretch of approximately 150 km. Each sampling station presents four microhabitats in the Uruguay River: rapids, island, margin and well; and one near the mouth of a tributary river: Santa Rosa River (PM), Amandaú River (PVC) and Rio Piratinim (SN). At all points, active collections were carried out from trawls with a mesh of 500 μm conical-cylindrical plankton. The variables: transparency, velocity, temperature, dissolved oxygen, electrical conductivity, pH, depth and river level were measured monthly. The samples collected were fixed in 4% formaldehyde, sorted and identified at the species level. The larval stages considered were: vitelline larval (LV), pre-flexion larval (LP), larval flexion (LF) and post-flexion larval (OLP). 1,523 larvae were captured, four orders, 14 families, 27 genera and 19 species. Of these, 92.12% belong to the Siluriform order, with the Pimelodidae family (89.43%) being the most abundant, being Parapimelodus valenciennis (50.10%), Pimelodus maculatus (15.30%) and Iheringichthys labrosus (8.14%). Migratory fish species were also captured: the Characiformes Megaleporinus obtusidens and Salminus brasiliensis and the Siluriformes Luciopimelodus pati, Pimelodus maculatus, Pseudoplatystoma corruscans and Sorubim lima. There was no statistically significant difference in larval distribution in the collection months (p> 0.05). Regarding the total larvae / 10m3 and the sampling stations, PVC had the highest densities (p <0.05). As for the larval stages and the sampling stations, LV presented the highest density in the PM station (p <0.05). For the larval stages of pre-flexion, flexion and post-flexion, there was a significant statistical difference (p <0.05), in which PVC presented the highest densities. The CCA revealed the most grouped and segregated wells and rapids of the island, margin and tributary (P <0.05) microhabitats. The CCA1 showed that water velocity (p <0.05), depth (p <0.05) and water transparency (p <0.05) were the most important factors for the distribution of larval stages. The LV stage (p <0.05) was positively correlated with water velocity and the greatest depth of the environment. Post-flexion larvae (p <0.05) were mainly related to greater transparency and inversely related to water depth and velocity. The NMDS revealed clear spatial segregation between the channel and island microhabitats of the margin and the tributary. According to the results, it is concluded that the PVC sampling station had the highest densities of fish larvae, and the micro-habitat Ilha represents the site of higher incidence of total larvae, which characterizes it as a nursery of fish larvae in initial stages, mainly Siluriformes.